2018
DOI: 10.1001/jama.2018.9432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Responsive Parenting Educational Intervention on Childhood Weight Outcomes at 3 Years of Age

Abstract: IMPORTANCE Rapid growth and elevated weight status in early childhood increase risk for later obesity, but interventions that improve growth trajectories are lacking.OBJECTIVE To examine effects of a responsive parenting intervention designed to promote developmentally appropriate, prompt, and contingent responses to a child's needs on weight outcomes at 3 years. DESIGN, SETTING, AND PARTICIPANTSA single-center randomized clinical trial comparing a responsive parenting intervention designed to prevent childhoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 35 publications
(68 reference statements)
4
114
2
3
Order By: Relevance
“…The outcomes of these interventions will tell us more about the effectiveness of interventions in differing contexts. Of the more recent trials, three have assessed outcomes to at least 2 years of age, and one trial has shown a similar reduction in BMI z score for infants in the intervention group, which broadly supports our findings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The outcomes of these interventions will tell us more about the effectiveness of interventions in differing contexts. Of the more recent trials, three have assessed outcomes to at least 2 years of age, and one trial has shown a similar reduction in BMI z score for infants in the intervention group, which broadly supports our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Future research will need to address how best to implement these effective interventions at scale and cost implications and determine which factors characterize successful interventions. This may include the addition of a sleep component to early intervention obesity prevention programmes …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a positive association between restriction and weight, but have primarily been observational (relying on parent‐reported restriction) or laboratory‐based experimental studies. Randomized controlled trials that promote nonrestrictive feeding practices (ie, responsive feeding) have demonstrated success in reducing childhood obesity through 1‐3 years of follow‐up . However, these are multi‐component interventions, and more research is needed to establish a causal link between parent feeding and obesity risk in children.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized controlled trials that promote nonrestrictive feeding practices (ie, responsive feeding) have demonstrated success in reducing childhood obesity through 1-3 years of follow-up. [25][26][27][28] However, these are multi-component interventions, and more research is needed to establish a causal link between parent feeding and obesity risk in children. Regardless, the improvements observed by our clinical program after families lifted restriction and increased structure are anecdotal evidence for the ecological validity of the empirical work to date.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown associations between demographic characteristics and infant weight, 23, 24 thus we examined potential confounding effects of maternal age, pre-pregnancy body mass index (BMI), and socioeconomic and marital status. Given previously reported positive effects of the INSIGHT responsive parenting (RP) intervention on early life weight outcomes, 25, 26 we explored study group (RP intervention vs. control) as a potential moderator. Return to work is associated with shorter breastfeeding duration.…”
Section: Introductionmentioning
confidence: 99%